The APOE gene cluster responds to air pollution factors in mice with coordinated expression of genes that differs by age in humans. Issue 2 (20th November 2020) - Haghani, Amin; Thorwald, Max; Morgan, Todd E.; Finch, Caleb E.
Abstract: Little is known of gene–environment interactions for Alzheimer's disease (AD) risk factors. Apolipoprotein E ( APOE ) and neighbors on chromosome 19q13.3 have variants associated with risks of AD, but with unknown mechanism. This study describes novel links among the APOE network, air pollution, and age‐related diseases. Mice exposed to air pollution nano‐sized particulate matter (nPM) had coordinate responses of Apoe ‐ Apoc1 ‐ Tomm40 in the cerebral cortex. In humans, the AD vulnerable hippocampus and amygdala had stronger age decline in APOE cluster expression than the AD‐resistant cerebellum and hypothalamus. Using consensus weighted gene co‐expression network, we showed that APOE has a conserved co‐expressed network in rodent and primate brains. SOX1, which has AD‐associated single nucleotide polymorphisms, was among the co‐expressed genes in the human hippocampus. Humans and mice shared 87% of potential binding sites for transcription factors in APOE cluster promoter, suggesting similar inducibility and a novel link among environment, APOE cluster, and risk of AD.